Living with mild brain injury : the difficulties of diagnosis and recovery from post-concussion syndrome - O'Connor, Pauline (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This important book presents a unique, personal account of the impact a mild traumatic brain injury can have. It tells the story of Pauline, who was 33 when a late football tackle caused a bleed in her brain which went undiscovered for 18 months. The account includes descriptions of hidden symptoms of concussion and post-concussion syndrome, pitfalls in diagnoses, the uneven progress of recovery and the effect of the varied reactions which others have to an acquired brain injury. The author incorporates memories alongside extracts from clinic notes, diary entries and emails to reflect the disjointed progress of diagnosis and recovery as- although similar- no two head injuries are the same. Through this book, the reader gains an appreciation of the confusion experienced by many brain injury survivors, which sheds light on why some may develop unusual behavior or mental health issues, and how such issues can be alleviated. Brain injuries are poorly understood by the general public and this can lead to difficult interactions. Moreover, complications in diagnosis means some may not realize they have this milder form of brain injury. This book will enlighten brain injury survivors and affected families and allow professionals an insight into their patients' experiences. As concerns grow over the risks which contact sports pose, this book shows how even mild brain injuries can wreak havoc with careers, relationships and one's sense of self, but that a happy life can still be found"--
OCLC-licensed vendor bibliographic record.
Keywords: Brain damage; Brain damage -- Diagnosis; Brain -- Wounds and injuries -- Complications; Brain damage -- Patients -- Rehabilitation; PSYCHOLOGY / Neuropsychology; HEALTH & FITNESS / Diseases / Nervous System (incl. Brain); SOCIAL SCIENCE / Handicapped